The Effectiveness of Utilizing Context Based Teaching Modules to Improve the Cognitive Abilities of Fourth Grade Students at SDN Unsongi - Asmi; Abdul Latief, Juraid; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the effectiveness of utilizing context based teaching modules in improving the cognitive abilities of students and to describe the process of its implementation in the fourth grade science (IPAS) learning at SD Negeri Unsongi. Data collection techniques include classroom observation, in depth interviews with teachers and students, questionnaire administration, and documentation of learning outcomes. The results indicate that the use of context based teaching modules is considered highly effective. Students show positive responses, with better comprehension levels, active involvement in classroom activities, and enthusiasm for material presented in a concrete and relevant manner. The module implementation is adapted to the science subject matter on the sub theme of utilizing and conserving natural resources within the context of students’ daily lives. The teacher successfully manages active and meaningful learning. Assessment simulations show an improvement in students’ cognitive abilities, with average scores reaching the good category. Students are able to connect the material with real life experiences and demonstrate critical and analytical thinking skills.